1993
DOI: 10.1172/jci116640
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbonic anhydrase inhibition on ventilation-perfusion matching in the dog lung.

Abstract: Lung carbonic anhydrase (CA) permits rapid pH responses when changes in regional ventilation or perfusion alter airway and alveolar Pco2. These pH changes affect airway and vascular resistances and lung compliance to optimize the balance of regional ventilation (VA) and perfusion (Q) in the lung. To test the hypothesis that these or other CA-dependent mechanisms contribute to VA/Q matching, we administered acetazolamide (25 mg/kg intravenously) to six anesthetized and paralyzed dogs and measured VA/Q relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…This rich diversity of expression has led some to search for nonclassical (i.e., non-acid-base) functions of the enzyme. Swenson et al (45) showed that CA inhibition impairs ventilation-perfusion matching in the lung, a process that is thought to result from both O 2 -and CO 2 -dependent changes in bronchial and vascular smooth muscle tone. To directly test whether CA inhibition alters HPV, a major mechanism that maintains ventillation perfusion (V A /Q) matching, Deem et al (7) found that AZ blunts and slows HPV in the isolated perfused rabbit lung.…”
Section: Discussionmentioning
confidence: 99%
“…This rich diversity of expression has led some to search for nonclassical (i.e., non-acid-base) functions of the enzyme. Swenson et al (45) showed that CA inhibition impairs ventilation-perfusion matching in the lung, a process that is thought to result from both O 2 -and CO 2 -dependent changes in bronchial and vascular smooth muscle tone. To directly test whether CA inhibition alters HPV, a major mechanism that maintains ventillation perfusion (V A /Q) matching, Deem et al (7) found that AZ blunts and slows HPV in the isolated perfused rabbit lung.…”
Section: Discussionmentioning
confidence: 99%
“…red cell and tissue CA inhibition) is <5 mg·kg -1 (250-350 mg) given every 8-12 h. This dose also inhibits vascular endothelial cell membrane CA IV and peripheral chemoreceptor CA. Although higher doses may increase ventilation further as respiratory acidosis develops, this comes at the expense of impairing CO 2 transport [4] and even ventilation-perfusion (V 'A/Q ') matching in the lung [41]. In healthy individuals this can be readily tolerated and even maximal exercise is possible with partial red cell CA inhibition [1,4], since the necessary compensatory hyperventilation does not exceed maximal voluntary ventilation (MVV) capacity.…”
Section: Clinical Application Of Ca Inhibitors As Respiratory Stimulantsmentioning
confidence: 99%
“…The benefits of CA inhibitors stem from the renal effect of mild metabolic acidosis which, at a dose of acetazolamide of 4-5 mg·kg -1 , is virtually maximal. The ventilatory stimulation that this affords is accompanied by insignificant effect on red cell CO 2 transport and efficiency of CO 2 elimination by the lungs [7,41]. Above this dose and the concentrations it achieves, CO 2 retention can be anticipated and the extra ventilation necessary to limit or prevent it may cause respiratory muscle fatigue.…”
Section: Hypoxaemic Lung Diseasementioning
confidence: 99%
“…In most studies in wNhich a conventional steady-state technique was used, end-tidal PCo2 was taken as an independent variable. However, in patients suffering from lung disease a relatively large P(a-ET),co2 gradient may be present wrhich, in addition, may be altered if lung carbonic anhydrase is inhibited (Swenson, Robertson & Hlastala, 1993 Swenson & Hughes (1993) show-ed that chronic and acute treatments with the drug led to different effects on the CO2 response curve. Although baseline ventilation w\as increased, they concluded that acute (intravenous) treatment has an inhibitory effect on the control of breathing.…”
Section: I Wagenaar Anid Othersmentioning
confidence: 99%